DIE LERNERGEBNISSE IN DESKRIPTIVEN SCHREIBFERTIGKEIT DER DEUTSCHEN SPRACHE KLASSE XI IIS 1 SMA NEGERI 1 MOJOSARI MIT DEM LERNMODELL ENTDECKUNG - LILIA SARI, GRAVITA (LATERNE, 2016)
In German language learning, students are required to be able to increase the ability to communicate orally and in writing. Writing skill is one of German language skills that is considered difficult by students. Based on observations made by the author, it is due to the low ability students of ideas / ideas, a lack of vocabulary in German, lack of mastery of language structure, and low motivation of students in writing German. To overcome these problems, need to be supported by an appropriate learning models. Learning model that can be used is a discovery learning model (discovery learning). The discovery learning model (discovery learning) is learning that regulates structure teaching with students actively involved in order to solve their own problems and find solution. This study aims to determine and describe the results of essay writing skills in learning German language in class XI IIS 1 by using discovery learning model. The method used is a qualitative research that will produce descriptive data. Sources of data in this study are 31 students of class XI IIS 1 SMA Negeri 1 Mojosari. The instrument used in this study is a written test. Data retrieval is executed in four meetings. The results show that, by using discovery learning model in essay writing skills in learning German languag in class XI IIS 1 SMA Negeri 1 Mojosari, the students can improve their learning outcomes that are originally bad to good, better and very good. It was shown from the average student learning outcomes increasingly. Keywords             : Writing Skills, Discovery Learning Model (Discovery Learning)